2021
DOI: 10.1111/dth.14919
|View full text |Cite
|
Sign up to set email alerts
|

Systemic antibiotics in hidradenitis suppurativa: efficacy and effects of body mass index and smoking pack‐year on the response to therapy

Abstract: The combination of oral clindamycin with rifampicin is recommended by European guidelines as a first‐line treatment in moderate‐to‐severe hidradenitis suppurativa (HS). Recent studies highlight that oral clindamycin in monotherapy (CM) may be a useful alternative treatment. We included 36 patients with a diagnosis of moderate‐to‐severe HS. A total of 19 patients were treated with combination oral clindamycin plus rifampicin (C + R) and 17 with oral CM for 12 weeks. The efficacy of CM vs C + R was analyzed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Obesity and DM are more prevalent in patients with HS than in those without HS ( 9 ). A retrospective study of 36 patients with HS by Iannone et al ( 11 ) stated that high body mass index (BMI) and smoking seemed to be predictive factors for poor treatment response to antibiotics. However, according to the multivariate analysis demonstrated in our study, obesity was not significantly associated with treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and DM are more prevalent in patients with HS than in those without HS ( 9 ). A retrospective study of 36 patients with HS by Iannone et al ( 11 ) stated that high body mass index (BMI) and smoking seemed to be predictive factors for poor treatment response to antibiotics. However, according to the multivariate analysis demonstrated in our study, obesity was not significantly associated with treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…IHS4 measures HS severity by assessing inflammatory nodules, abscesses, and draining fistulas ( 5 ). Antibiotics are more effective against nodule and abscess than against fistula ( 11 ). In our study, IHS4 total score, which reflects the severity of inflammatory lesions, correlated well with patients’ response to first-line antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clindamycin and rifampicin used at a dose of 300 mg twice daily have been proven effective in HS in several observational studies 65,6769 and are considered a first-line and second-line treatment for HS. A systematic review of retrospective and prospective series reported response rates from 71% to 93% in 187 patients, strongly favoring their use.…”
Section: Treatmentmentioning
confidence: 99%
“…65 Likewise, a retrospective study comparing the efficacy of lymecycline (300 mg daily) versus the combination therapy clindamycin and rifampicin (600 mg plus 600 mg daily) during 10 weeks in 52 patients (26 per group) observed a 57.7% and 53.8% HiSCR achievement, respectively. 66 Clindamycin and rifampicin used at a dose of 300 mg twice daily have been proven effective in HS in several observational studies 65,[67][68][69] and are considered a first-line and second-line treatment for HS. A systematic review of retrospective and prospective series reported response rates from 71% to 93% in 187 patients, strongly favoring their use.…”
Section: Topical Treatmentmentioning
confidence: 99%
“…Hidradenitis suppurativa (HS) is a chronic relapsing skin inflammatory disease. The therapeutic management of HS is based on immunosuppressive therapies (steroids, dapsone, cyclosporine) or immunomodulatory therapies (antibiotics or biological drugs) 3 . The Hidradenitis Suppurativa Foundation from North America experts (HSF), based on real-life data and pathogenetic mechanisms of lethal COVID-19 cases, recommend to continue current biological treatment such as TNF-α, IL-12/IL-23 and IL-17 inhibitors suspending treatment only in case of COVID-19 suspicious symptoms 4 .…”
Section: To the Editormentioning
confidence: 99%